Introduction to the Special Issue: 'Governing Climate‐altering Approaches'. (25th April 2021) - Pasztor, Janos; Harrison, Nicholas
Abstract: While awareness of the global climate emergency is growing, so too are greenhouse gas emissions and a persistent gap remains between international commitments and the 1.5–2°C goal of the Paris Agreement. Additional climate‐altering approaches are being considered to reduce atmospheric concentrations of carbon dioxide ( carbon dioxide removal ) or the amount of absorbed solar energy in the climate system ( solar radiation modification ) but they face multiple uncertainties and knowledge gaps relating to their feasibility, acceptability, sustainability and governance. This special issue presents new insights relating to the governance of climate‐altering approaches together with possible ways to address knowledge and governance gaps in future. Abstract : Recent UN reports suggest that despite commitments to reduce greenhouse gas emissions, atmospheric concentrations continue to rise. Additional approaches known as carbon dioxide removal and solar radiation modification are being considered but face multiple uncertainties. This special issue addresses some of the governance gaps around these climate‐altering approaches.